2012
DOI: 10.1111/j.1475-1313.2012.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and demographic characteristics of deafblindness rehabilitation clients in Montréal, Canada

Abstract: The age distribution in this sample of persons with dual sensory impairment indicates that service delivery planning will need to strongly consider the growing presence of older adults as the baby-boomers approach retirement age. The distribution of their visual and auditory limits indicates that the large majority of this client group has residual vision and hearing that can be maximized in the rehabilitation process in order to restore functional abilities and social participation. Future research in this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 25 publications
4
75
1
1
Order By: Relevance
“…In a Danish study of DSL rehabilitation clients Dammeyer (2013) found that DSL increased rapidly in those aged 65 years and over. In a similar Canadian study Wittich et al (2012) found that 69% of DSL rehabilitation clients were aged 65 years and over. According to Caban et al (2005) DSL increased from 1.3% for 18 to 44 year olds to 6.6% in those aged 80 years and older.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a Danish study of DSL rehabilitation clients Dammeyer (2013) found that DSL increased rapidly in those aged 65 years and over. In a similar Canadian study Wittich et al (2012) found that 69% of DSL rehabilitation clients were aged 65 years and over. According to Caban et al (2005) DSL increased from 1.3% for 18 to 44 year olds to 6.6% in those aged 80 years and older.…”
Section: Introductionmentioning
confidence: 94%
“…Public awareness of DSL is also not widespread and in turn, rehabilitation options have not been well-explored in many countries. Exceptions to this are discussed in papers emerging from the US, Canada and Australia (Heine and Browning, 2002; Saunders and Echt, 2007, 2012; Wittich et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has also however indicated that there is an increasing dual sensory impairment i.e. vision and hearing loss among older adults (Wittich et al, 2012).…”
Section: Several Categories Also Belonged To Chapter 8 Major Life Armentioning
confidence: 99%
“…Most DSL patients have residual vision and residual hearing, which can be optimized through rehabilitation (Wittich et al 2012). However, because of the multiplicative effect, the current "unisensory" rehabilitation practice may not be sufficient for DSL patients.…”
Section: Introductionmentioning
confidence: 96%